Green strategy for sustainable waste-to-energy supply chain - Lam, H.; Ng, Wendy; Ng, R.; Ng, E.; Abdul Aziz, M.; Ng, D. (Pergamon, 2013)
In this paper, a green strategy for systematic design of waste-to-energy supply chain is proposed. The presented green strategy includes efficient resources management and reduction of carbon footprint of a waste-to-energy supply chain. A novel two-stage optimisation model (macro- and micro-stage) is developed in this work. Micro-stage involves the optimisation and allocation of waste (e.g., biomass, industrial waste, etc.), as well as the design of integrated processing hub. Meanwhile, macro-stage handles the synthesis and optimisation of waste-to-energy supply network. Based on the optimised result, the operation and logistics management of the waste can be determined. In addition, the optimum technologies which convert waste into value-added products are determined. An actual case study that geographically based on west coast of Peninsular Malaysia was developed to illustrate the proposed strategy.